2017
DOI: 10.1111/1475-6773.12667
|View full text |Cite
|
Sign up to set email alerts
|

Home Health Care: Nurse–Physician Communication, Patient Severity, and Hospital Readmission

Abstract: Poor communication between home health nurses and physicians is associated with an increased risk of hospital readmission among high-risk patients. Efforts to reduce readmissions among this population should consider focusing attention on this factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 7 publications
0
43
0
1
Order By: Relevance
“…Prediction of readmission is critically important to reduce readmissions for home health care patients. The readmission rate is high, around 30-100% among such patients, and greatly impacts the whole health system [3,14]. Those home care patients usually have a certain degree of disability and are quite vulnerable after leaving the hospital; such a significant jump between the hospital and home requires preventive interventions with more insight into patient health at home.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of readmission is critically important to reduce readmissions for home health care patients. The readmission rate is high, around 30-100% among such patients, and greatly impacts the whole health system [3,14]. Those home care patients usually have a certain degree of disability and are quite vulnerable after leaving the hospital; such a significant jump between the hospital and home requires preventive interventions with more insight into patient health at home.…”
Section: Introductionmentioning
confidence: 99%
“…10 In another recent study, researchers found that the presence of communication failures between HHC and physicians was associated with a nearly 10% increase in the probability of hospital readmission among high-risk HHC patients with HF. 11 Our study illustrates that unclear accountability and inadequate communication likely contribute to medication errors and suboptimal safety for both HHC nurses and patients, which may in turn contribute to adverse patient outcomes such as readmissions.…”
Section: Discussionmentioning
confidence: 85%
“…10 In addition, communication failures between HHC nurses and physicians have been found to increase the probability of hospital readmission by nearly 10% in high-risk patients with HF who receive HHC at discharge. 11 As a partner in the continuum of care, nurses provide a majority of HHC services and have a critical role in crafting and implementing a patient's plan of care after discharge. 12,13 An evaluation of Medicare home health practices found that nurses completed over 98% of the first HHC visits for Medicare patients.…”
Section: Introductionmentioning
confidence: 99%
“…Poor communication between community nurse and physician is associated with an increased risk of hospital readmission among high‐risk patients …”
Section: Methodsmentioning
confidence: 99%